RELATIONSHIP BETWEEN SCHOOL PHYSICAL ENVIRONMENT AND CO-CURRICULAR ACTIVITIES IN PRIVATE PRIMARY SCHOOLS. A CROSS-SECTIONAL STUDY. - Ampaire, Stella; Nwana, Kevin (Student’s Journal of Health Research Africa, 2024)
Background Co-curricular activities are seen as a way of enhancing students’ academic, social, and personal development, as well as preparing them for future careers. The study aims to assess the relationship between the school’s physical environment and co-curricular activities in private primary schools. Methodology The study adopted a descriptive, correlational, and cross-sectional survey design. The study was carried out in selected private primary schools in Fort Portal City. Fort Portal City is located in western Uganda, in the Kabarole District. The researcher ensured quantitative data was collected using questionnaires. Simple random sampling was used to select 196 respondents. Results The majority of the respondents were male 58.3% while females were 41.7%. The largest age group consisted of respondents below 20 years, mainly pupils, representing 66.1% of the total sample. The Pearson Correlation coefficient of 0.682** indicates a strong positive correlation between the school’s physical environment and the pupil’s participation in co-curricular activities. A strong positive relationship (R = 0.714) between the school’s physical environment and the pupil’s participation in co-curricular activities. The R Square value of 0.509 indicates that approximately 50.9% of the variance in pupil participation can be explained by the school’s physical environment. The Unstandardized Coefficient for the school’s physical environment is 3.214. Conclusion Further, findings showed a strong positive relationship between the school’s physical environment and pupil’s participation in co-curricular activities within private primary schools in Fort Portal City. Recommendations Private schools should allocate resources to enhance the school’s physical infrastructure, including sports facilities, recreational areas, and amenities, to create an attractive and functional environment that promotes student engagement in co-curricular activities.